2017
DOI: 10.1080/15384101.2017.1295177
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 recruitment to damaged DNA sites is dependent on CDK9

Abstract: Double strand break lesions, the most toxic type of DNA damage, are repaired primarily through 2 distinct pathways: homology-directed recombination (HR) and non-homologous end-joining (NHEJ). BRCA1 and 53BP1, 2 proteins containing the BRCT modular domain, play an important role in DNA damage response (DDR) by orchestrating the decision between HR and NHEJ, but the precise mechanisms regarding both pathways are not entirely understood. Previously, our group identified a putative interaction between BRCA1 and BA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…BRCA1 C-terminal (BRCT) domains are restricted to a specialized group of only 23 proteins that are predominantly associated with DNA damage response (DDR) pathways 13 . The BRCT domain serves as a scaffold for organizing multi-protein complexes that orchestrate the decision between homologous recombination (HR) and non-homologous end joining (NHEJ) through the recruitment of specific repair proteins to sites of DNA damage 47 . In the human proteome, CTDP1 is the only phosphatase that also encodes a BRCT domain 1 , suggesting it could play a unique role by regulating the phosphorylation-mediated signaling involved in the DDR.…”
Section: Introductionmentioning
confidence: 99%
“…BRCA1 C-terminal (BRCT) domains are restricted to a specialized group of only 23 proteins that are predominantly associated with DNA damage response (DDR) pathways 13 . The BRCT domain serves as a scaffold for organizing multi-protein complexes that orchestrate the decision between homologous recombination (HR) and non-homologous end joining (NHEJ) through the recruitment of specific repair proteins to sites of DNA damage 47 . In the human proteome, CTDP1 is the only phosphatase that also encodes a BRCT domain 1 , suggesting it could play a unique role by regulating the phosphorylation-mediated signaling involved in the DDR.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, its loss results in spontaneous replication stress and genetic instability [ 10 ]. CDK9 also promotes DNA double-strand break (DSB) repair by homologous recombination (HR) by facilitating recruitment of the BRCA1 breast tumor suppressor protein to DNA damage sites [ 6 ] and associates with Ku70, which is involved in DSB repair by non-homologous end joining (NHEJ) [ 5 ]. CDK9's role in promoting genome integrity is regulated at least in part through deacetylation by the SIRT2 sirtuin deacetylase and breast tumor suppressor protein, which promotes its kinase activity [ 11 ] and in turn phosphorylates UBE2A and directs H2Bub1 and PCNA ubiquitinylation [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…High expression of BRCA1 has been shown to correlate with lower overall survival in glioblastoma patients [ 61 ], underscoring the need to investigate treatments that can dysregulate BRCA1 signaling. Importantly, CDK9 has been shown to modulate the recruitment of BRCA1 to DSBs and plays an important role in the BRCA1-mediated homologous recombination (HR) DNA repair process ( Figure 2 E) [ 62 ]. Cell survival assays performed in wild-type BRCA1 mammary gland carcinoma cells, for example, demonstrated that knockdown of CDK9 impaired recruitment of BRCA1 to DSBs and sensitized cells to radiation [ 62 ].…”
Section: Impact Of Cdk9 Inhibition On Cancer Cellsmentioning
confidence: 99%